Strategi Guru dalam Membentuk Karakter Disiplin Siswa Sekolah Dasar di Era Globalisasi - Puspita, Oxsyana Nabila; Shalahuddin, Abdullah Hafizh; Setyaningrum, Rahmada Fitradewi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The negative effects of globalization mean that the younger generation has lost ethics. Deterioration of character still often occurs in school children whose actions and attitudes conflict with religious and ethical principles. School is a strategic place to teach disciplinary behavior because it allows someone to follow the rules. Disciplined behavior is one of the most important behaviors to teach. This research aims to discuss teacher strategies in shaping students' disciplinary character in the era of globalization. The method used in this research is qualitative, sourced from library data, and involves identifying sources from books, papers, articles and journals. The analysis technique used in this research is Content Analysis. The results of the research show that students' disciplined character can be formed through a values ​​approach, making school regulations, taking a values ​​clarification approach in the form of punishments and rewards, as well as habituating students.